A modeling of the oxygen regime in bioreactors-aerotanks at the purification of waste waters from organic pollutants - Airapetian, T.S.; Telyma, S.V.; Oliynik, O.Ja. (Reports of the National Academy of Sciences of Ukraine, 2017)
A mathematical model of the oxygen supply for the biological purification of waste waters from organic pollutants in aerotanks with suspended and fixed biocenoses is presented. The features of a modeling of the oxygen regime at the purification in the aerotanks-mixers and aerotanks-displacers are considered.